In-situ stress characteristics and rockburst prediction for a tunnel in a high in-situ stress environment - Luo, Chun; Shen, Zhiwen; Zhang, Jin; Yao, Maohong; Yang, Ying; Zhang, Kai; Wang, Meng; Yang, Shuang; Zhang, Yonggang (Frontiers in Earth Science, 2025)
As the main source of pressure around tunnel rock masses, in-situ stress must be thoroughly understood to accurately predict the potential for rockburst events, especially in high-stress construction environments. Yet, theoretical advancements in this field remain behind practical engineering demands. In this study, we used a multiple linear regression approach to determine the initial in-situ stress field across the entire Ping’an tunnel and employed strength theory to predict rockburst occurrence. The regression results closely match field measurements, and the consistently low p-values confirm the reliability of the model. In addition, the rockburst intensity predicted based on the strength criterion shows strong agreement with real-world engineering observations, demonstrating the rationality of the proposed methodology. The findings from this research contributes to a deeper understanding of the initial in-situ stress field in rockburst-prone tunnels under high in-situ stress conditions and provide a scientific basis for tunnel alignment optimization and rockburst risk assessment. These insights hold significant practical implications for the construction of similar projects.